Efficacy of marine bioactive compound fucoidan for bone regeneration and implant fixation in sheep. Issue 4 (18th November 2021) - Nielsen, Mads Suhr; Mikkelsen, Maria Dalgaard; Ptak, Signe Helle; Hejbøl, Eva Kildall; Ohmes, Julia; Thi, Thuan Nguyen; Nguyen Ha, Vy Tran; Fretté, Xavier; Fuchs, Sabine; Meyer, Anne; Schrøder, Henrik Daa; Ding, Ming
Abstract: The need for a substitute for allograft and autograft is rising as bone graft surgeries exceed available supplies. We investigated the efficacy of the low‐molecular weight marine bioactive compound fucoidan (FUC) on bone regeneration and implant fixation in seven female sheep, as FUC has shown great promise as a bone substitute. Titanium implants were inserted bilaterally in the distal femurs to test three hydroxyapatite/fucoidan (HA/FUC) groups and compared to allograft. The HA was coated with either 500 or 1500 μg of FUC, obtained by microwave‐assisted chemical extraction, or 500 μg of FUC obtained by an enzyme‐assisted extraction method. The concentric 2‐mm gap around the implant was filled with either one of the HA/FUCs or allograft from the donor sheep. After 12 weeks, implant–bone blocks were harvested and divided into three parts for mechanical push‐out testing, immunohistochemistry, and micro‐CT and histomorphometry. Pronounced bone formations were observed by micro‐CT and histomorphometry in all groups, but higher bone volume fractions were seen in the allograft group compared to the three HA/FUC groups. The trabecular thickness, trabecular separation, and architectural anisotropy were all significantly higher in the allograft group compared to the three HA/FUC groups. In conclusion, adequate bone formation was observed in all groups, although the bone formation was significantly greater in the allograft group. Also, no significant differences existed in the shear mechanical properties between groups, suggesting that the combination of HA and FUC can achieve a similar fixation strength to allograft in this model.